CODE SWITCHING USED BY ENGLISH TEACHER IN TEACHING ENGLISH AT THE SECOND GRADE OF SMAN 1 AEK NATAS - Ismi Darlina; Indra Hartoyo (Universitas Negeri Medan, 2021)
The aims of this study were to find out the types of code switching used by English teacher and to investigate the reasons why the English teacher used code switching in Teaching English. This study was conducted by using descriptive qualitative method. The data were collected through observing, interview, and recording. The analysis of code switching was based on Poplack’s theory to know the types of code switching and Hoffman’s theory to ivestigate the reasons why the teacher used code switching. Based on the analysis, it was found that there were 106 utterances that has been categorized as code swutching consisting of 46 intra-sentential, 28 inter-sentential, and 32 tag switching. The reasons why teacher used code switching in teaching English process were Quoting somebody else, Interjection and Repetition used for clarification, there were two reasons set by the teacher, there were to make the students understand about the explanation given by the teacher and to develop student’s English skill.Keywords: Code Switching, English Teacher, Teaching English